Here is a trick,

A trick that is trick.

It makes a problem

That is rather sticky!

First you take 'a'

And then you take 'b'

You then make them equal.

It's easy you see?

a = b

You then square both sides

And what do you get?

'a' squared and 'b' squared,

You got that I'll bet!

a^2 = b^2

But don't you remember

The first thing I said?

'a' equals 'b'

So I'll write this instead!

a^2 = ab

But we don't want to make

'b' squared feel unloved!

So we will subtract it

From both sides up above.

a^2 - b^2 = ab - b^2

Now the next step

That we must complete

Is to factor both sides,

It's really quite neat!

(a + b) (a - b) = b (a - b)

But don't you forget!

You must simplify.

Divide by 'a' minus 'b'

And wave it "bye-bye!"

(a + b) = b

Remember that rule

I made WAY back when?

Well now it is time

To use it again!

b + b = b

But don't you forget

To combine all like terms!

'b' plus 'b' is '2b'

It's just like you learned!

2b = b

Now divide through by 'b'

And what's left behind?

Why two equals one

Is what you will find!

2 = 1